2008
DOI: 10.1007/s00595-006-3640-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic configurations of the recurrent laryngeal nerve and inferior thyroid artery

Abstract: Key words Inferior laryngeal nerve · Recurrent laryngeal nerve · Inferior thyroid artery · Thyroidectomy · Nerve injuryWe read with interest the paper by Yih-Huei Uen et al. 1 concerning the surgical anatomy of the recurrent laryngeal nerves published in the April 2006 issue of Surgery Today.Our comments are as follows.(1) Although much attention has been given to the protection of the recurrent laryngeal nerve (RLN) in thyroid surgery, cases of RLN injury are still occasionally reported in the literature. 2 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…En su trayecto hacía la laringe, el nervio laríngeo recurrente tiene múltiples variaciones anatómicas. En los trabajos de Makay, Shao y Yalexin se han descrito hasta 20 variantes [10][11][12] , lo que explica por qué de 20 a 30 % de las lesiones quirúrgicas de una ramificación terminal no producen secuelas funcionales en la cuerda vocal ipsilateral y, asimismo, el peligro de las lesiones quirúrgicas desapercibidas con técnicas operatorias sin visualización directa del nervio laríngeo recurrente.…”
Section: Revisión Del Tema Y Discusiónunclassified
“…En su trayecto hacía la laringe, el nervio laríngeo recurrente tiene múltiples variaciones anatómicas. En los trabajos de Makay, Shao y Yalexin se han descrito hasta 20 variantes [10][11][12] , lo que explica por qué de 20 a 30 % de las lesiones quirúrgicas de una ramificación terminal no producen secuelas funcionales en la cuerda vocal ipsilateral y, asimismo, el peligro de las lesiones quirúrgicas desapercibidas con técnicas operatorias sin visualización directa del nervio laríngeo recurrente.…”
Section: Revisión Del Tema Y Discusiónunclassified
“…These variations can occur in the pattern of division, relations of the nerve to the inferior thyroid artery and its branches and the existence of the nerve in a non-recurrent fashion (1)(2)(3). It is worth noting that up to 28 variations have been described in anatomy studies (2). Similarly, variations have been assessed relative to the ligament of berry and the tubercle of Zuckerkandl (3).…”
Section: Anatomic Variationsmentioning
confidence: 99%
“…But for the surgeon, it is easier to look at these variations relative to the inferior thyroid artery and its branches as the surgeon has to always address this artery as a step in thyroid surgery. One way is to classify the recurrent laryngeal nerve into type A (anterior to the artery), type B (between branches of the artery) or type C (posterior to the artery) (1,2). In a systematic review and meta analysis of 32 papers with 8655 recurrent laryngeal nerve sides assessing for the anatomic variation of the nerve relative to the inferior thyroid artery, Ling et al found the nerve to anterior (type A) in 20%, in between the branches (type B) in 28% and posterior(type C) in 52% of the cases (1).…”
Section: Anatomic Variationsmentioning
confidence: 99%
See 2 more Smart Citations